2019
DOI: 10.1021/acs.inorgchem.9b00219
|View full text |Cite
|
Sign up to set email alerts
|

A Series of Lanthanide-Based Metal–Organic Frameworks Derived from Furan-2,5-dicarboxylate and Glutarate: Structure-Corroborated Density Functional Theory Study, Magnetocaloric Effect, Slow Relaxation of Magnetization, and Luminescent Properties

Abstract: Herein, through a dual-ligand strategy, we report eight isorecticular lanthanide(III) furan-2,5-dicarboxylic acid metal−organic frameworks (Ln-MOFs) with the general formula {[Ln(2, Gd (3), Tb (4), Dy (5), Ho (6), Er (7), and Yb (8); 2,5-FDA 2− = furan-2,5-dicarboxylate and Glu 2− = glutarate; x = 0.5 for 1, 2, and 4 and x = 0 for 3 and 5−8], synthesized under solvothermal conditions by using an N,N′-dimethylformamide/H 2 O mixed solvent system. Crystallographic data reveal that all eight Ln-MOFs 1−8 crystall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(55 citation statements)
references
References 116 publications
4
51
0
Order By: Relevance
“…[13][14][15][16] Rare-earth (RE) metals, which include scandium, yttrium and the fifteen lanthanides, have been used to synthesize a diverse library of MOFs, including many with unique structures and properties driven by the high coordination numbers and geometries of RE-metals. [17][18][19][20] Like other classes of MOFs, RE-MOFs have been reported with several different secondary building units (SBUs), including inorganic nodes that are metal ions, 21,22 chains, [23][24][25] or clusters. 5,[26][27][28][29] In 2013, Eddaoudi et al showed that the use of fluorinated modulators, such as 2-fluorobenzoic acid, favors the formation of RE-cluster nodes, instead of the ion or chain nodes that tend to preferentially form in the presence of carboxylic acid linkers.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16] Rare-earth (RE) metals, which include scandium, yttrium and the fifteen lanthanides, have been used to synthesize a diverse library of MOFs, including many with unique structures and properties driven by the high coordination numbers and geometries of RE-metals. [17][18][19][20] Like other classes of MOFs, RE-MOFs have been reported with several different secondary building units (SBUs), including inorganic nodes that are metal ions, 21,22 chains, [23][24][25] or clusters. 5,[26][27][28][29] In 2013, Eddaoudi et al showed that the use of fluorinated modulators, such as 2-fluorobenzoic acid, favors the formation of RE-cluster nodes, instead of the ion or chain nodes that tend to preferentially form in the presence of carboxylic acid linkers.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14] Therefore, Gd(III)-based inorganic polymers, MOFs, and CPs with possible large magnetic and physical densities as well as weak magnetic interactions have received much attention from researchers. [15][16][17] To obtain Gd(III)-based inorganic polymers, MOFs, and CPs with a large ΔS m under low fields, a key point is to choose suitable Gd III -ion sources and ligands. 18,19 Gd III salts, including Gd(NO 3 ) 3 , GdCl 3 , Gd 2 (SO 4 ) 3 , GdPO 4 , and Gd 2 (CO 3 ) 3 , are the most common Gd III -ion sources because of their relatively good solubility in common solvents.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16] Rare-earth (RE) metals, which include scandium, yttrium and the fifteen lanthanides, have been used to synthesize a diverse library of MOFs, including many with unique structures and properties driven by the high coordination numbers and geometries of RE-metals. [17][18][19][20] Like other classes of MOFs, RE-MOFs have been reported with several different secondary building units (SBUs), including inorganic nodes that are metal ions, 21,22 chains, [23][24][25] or clusters. 5,[26][27][28][29] In 2013, Eddaoudi et al showed that the use of fluorinated modulators, such as 2-fluorobenzoic acid, favors the formation of RE-cluster nodes, instead of the ion or chain nodes that tend to preferentially form in the presence of carboxylic acid linkers.…”
Section: Introductionmentioning
confidence: 99%